EVALUATION OF RISK FACTORS AND THEIR PROGNOSTIC VALUE IN PATIENTS WITH ISCHEMIC STROKE - CHANDRA SHEKAR K; POLISETTI, HIMA SREE; K, KARTHIKEYA; KR, VINAY RAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of this study were to evaluate the risk factors in patients with ischemic stroke, to find out the prognosis of ischemic stroke regarding risk factors, and to identify the patients having modifiable risk factors so that care can be taken to prevent recurrences. Methods: This was a prospective and observational study with 100 patients with ischemic stroke. Patients were recruited from November 2017 to October 2018. NIHSS score was used to classify the severity of the stroke. The Barthel index was used to assess prognosis at the time of discharge. Results: The mean age of the study population was 61.4±13.7 years. There was no statistically significant (p=0.28) difference in the outcome of the patients with respect to gender. There was a statistically significant (p=0.04) difference in the severity of the patients respective to gender. Among 100 patients, 55 had hypertension and the relative risk of hypertension was found to be 1.22, indicating hypertension is the most predominant risk factor. Conclusion: Hypertension is the most prevalent risk factor in the present study. As per our study findings, hypertension, diabetes mellitus, a history of smoking, and a history of alcohol intake were the preventable risk factors, leading to severe stroke and poor functional outcome. Patients with multiple risk factors had severe stroke and poor functional outcome when compared to patients with single or no risk factors. Patients with severe stroke based on NIHSS score had the poor functional outcome.